Karta sredneĭ chasti Tatarskago proliva otʺ zaliva De-Kastri do bukhty Grossevicha sostavlena po gidrograficheskim i topograficheskim rabotam chinov Morskogo i Voennago Vi︠e︡domstv s 1879-1900 g. Izdana Glavnymʺ Gidrograficheskimʺ Upravleniem vʺ 1902 g. / Kopirovalʺ khim. tushʹi︠u︡ G. Elʹshinʺ - Russia. Glavnoe gidrograficheskoe upravlenīe (Sankt-Peterburg : Morskoe ministerstvo, Glavnoe gidrograficheskoe upravlenīe; [Санкт-Петербург] : Морское министерство, Главное гидрографическое управленіе, 1902)
Relief shown by hachures and spot heights. Depths shown by soundings and isolines.; Greenwich meridian.; Main title translation: Map of the middle part of the Tatar Strait from De-Kastri Bay to Grossevich Bay compiled from the hydrographic and topographic work of the naval and military departments from 1879-1900. Published by the Main Hydrographic Office in 1902.; Includes three inset maps: Plan of Imperatorskaya Gavan -- Plan of Korsakov Bay -- Plan of anchorage on the Sertunai river and Putyatinsky coal mines.; Inset maps: Planʺ Imperatorskoĭ gavani -- Planʺ bukhty Korsakova -- Planʺ i︠a︡kornago mi︠e︡sta u ri︠e︡ki Sertunaĭ u Puti︠a︡tinskikhʺ kamennougolʹnykhʺ kopeĭ.; "Masshtabʺ 6 milʹ v di︠u︡ĭmi︠e︡ (1/438480)" = Scale 6 miles in 1 inch.; "No. 593" -- bottom right margin Color; 1:438,480